Multi-step encapsulation of chemotherapy and gene silencing agents in functionalized mesoporous silica nanoparticles. Issue 16 (11th April 2017) - Shen, Jianliang; Liu, Haoran; Mu, Chaofeng; Wolfram, Joy; Zhang, Wei; Kim, Han-Cheon; Zhu, Guixian; Hu, Zhongbo; Ji, Liang-Nian; Liu, Xuewu; Ferrari, Mauro; Mao, Zong-Wan; et al.
Abstract : The combination therapy of a mutilfunctional porous silica nanoplatform with capability of codelivering chemo/siRNA therapeutics, which was superior to chemo monotherapy. Abstract : Drug to carrier ratio is an important consideration in designing drug platforms, since a low loading capacity necessitates the use of high doses of carriers, which can result in side effects. Here, we have engineered a platform to co-deliver small molecule drugs and small interfering RNA (siRNA). This platform consists of cyclodextrin-grafted polyethylenimine (CP) functionalized mesoporous silica nanoparticles (MSNP). A unique multi-step encapsulation procedure was used to obtain a high loading capacity for doxorubicin (DOX) and siRNA oligos specific for the PKM2 gene that encodes pyruvate kinase M2, an enzyme catalyzing the final rate-limiting step in glycolysis. We systematically characterized this platform (CP-MSNP@DOX/PKM2) in vitro and evaluated its therapeutic efficacy in vivo with a mouse model of triple negative breast cancer (TNBC). Exposure of TNBC cells to CP-MSNP@DOX/PKM2 resulted in suppressed target gene expression, reduced cell proliferation, and enhanced apoptosis. Intravenous administration of the drug substantially decreased the tumor burden in comparison to DOX or siRNA monotherapy. In conclusion, we have developed a platform for efficient co-delivery of small molecule drugs and therapeutic siRNA.